Dielectric Front Passivation for Cu(In,Ga)Se2 Solar Cells: Status and Prospect - Jessica de Wild; Romain Scaffidi; Guy Brammertz; Gizem Birant; Bart Vermang (Advanced Energy & Sustainability Research, 2023)
Cu(In,Ga)Se2 (CIGSe) solar cells are among the most efficient thin‐film solar cells on lab scale. However, this thin‐film technology has relatively large upscaling losses for commercial technology. To tackle this, paradigm shifts are proposed that allow for simpler, cost‐effective, and efficient CIGSe solar cells. Front passivation using dielectric layers is one of the options being investigated as this is widely used in Si technology. Research on front passivation for CIGSe is in an early stage and no improvements are made yet. A close comparison with silicon technology is made to understand why it seems to be more difficult for CIGSe solar cells. In general, chemical passivation is less effective, resulting in higher interface defect densities than seen for Si. Also, field‐effect passivation requires positive charges, which have not been implemented yet on the CIGSe front surface. Finally, for Si passivation, often a high‐temperature annealing step is applied, which is not possible for CIGSe. It is proposed to apply a dielectric tunneling layer with positive fixed charges in combination with an electron transport layer to move forward. A list of potential dielectric layers that could be suitable for CIGSe is provided.